Математична модель оптимальної структури вугільної продукції для ТЕС України - Stohniy O.V.; Makortetskiy M.M.; Perov M.O. (General Energy Institute of the National Academy of Sciences of Ukraine, 2013)
Сurrent situation in the Ukrainian power sector, characterized by a limited access to power resources of domestic production, requires use of solid fossil fuels, such as the coal. Providing national TPPs with a required quantity of coal products is an important factor both in terms of energy independence of the country and environmental situation, which is essentially harmed by burning the high-ash coal.The aim of this work is to develop a mathematical optimization model to provide domestic TPPs with coal products of established (passport ) thermal properties at a minimum price. Development of an algorithm implementing this model provides for indicators of the coal products quality, which are crucial in calculating the price of this product.To achieve this goal, a meaningful and mathematical formulation of the problem is developed along with an algorithm and software means to solve it.Solution of the problem provides an optimal structure of fuel stocks with valid parameters of quality at lowest cost in the power generating industry of the country.The provided model was tested at optimizing coal production structure at 6 TPPs that consume anthracite and lean coal, and results of the test proved its adequacy with regard to the object of the study.